Oxidized LDL‐dependent pathway as new pathogenic trigger in arrhythmogenic cardiomyopathy. Issue 9 (2nd August 2021) - Sommariva, Elena; Stadiotti, Ilaria; Casella, Michela; Catto, Valentina; Dello Russo, Antonio; Carbucicchio, Corrado; Arnaboldi, Lorenzo; De Metrio, Simona; Milano, Giuseppina; Scopece, Alessandro; Casaburo, Manuel; Andreini, Daniele; et al.
Abstract: Arrhythmogenic cardiomyopathy (ACM) is hallmarked by ventricular fibro‐adipogenic alterations, contributing to cardiac dysfunctions and arrhythmias. Although genetically determined (e.g., PKP2 mutations), ACM phenotypes are highly variable. More data on phenotype modulators, clinical prognosticators, and etiological therapies are awaited. We hypothesized that oxidized low‐density lipoprotein (oxLDL)‐dependent activation of PPARγ, a recognized effector of ACM adipogenesis, contributes to disease pathogenesis. ACM patients showing high plasma concentration of oxLDL display severe clinical phenotypes in terms of fat infiltration, ventricular dysfunction, and major arrhythmic event risk. In ACM patient‐derived cardiac cells, we demonstrated that oxLDLs are major cofactors of adipogenesis. Mechanistically, the increased lipid accumulation is mediated by oxLDL cell internalization through CD36, ultimately resulting in PPARγ upregulation. By boosting oxLDL in a Pkp2 heterozygous knock‐out mice through high‐fat diet feeding, we confirmed in vivo the oxidized lipid dependency of cardiac adipogenesis and right ventricle systolic impairment, which are counteracted by atorvastatin treatment. The modulatory role of oxidized lipids on ACM adipogenesis, demonstrated at cellular, mouse, and patient levels, represents a novel risk stratification tool and a target for ACM pharmacological strategies. Synopsis: ACM mutations are necessary but not sufficient for disease penetrance. The contribution of oxidised lipids as novel pharmacologically targetable cofactors was demonstrated by a multi‐layer approach (patients – in vitro – in vivo ), leading to an advancement in the knowledge of ACM pathogenesis. ACM patients show high oxLDL plasma levels, which stratify ACM phenotype severity. oxLDL worsen adipogenic differentiation of ACM cells by altering the CD36/13HODE/PPARγ axis. By increasing oxLDL in an ACM mouse model with low penetrance, ACM‐specific tissue remodelling, functional and electrical impairments are unveiled. NAC and Atorvastatin can prevent ACM phenotypes in vitro / in vivo . Abstract : ACM mutations are necessary but not sufficient for disease penetrance. The contribution of oxidised lipids as novel pharmacologically targetable cofactors was demonstrated by a multi‐layer approach (patients – in vitro – in vivo ), leading to an advancement in the knowledge of ACM pathogenesis.